Analisis Kecakapan Komunikasi Matematis Siswa SMP dalam Menyelesaikan Soal Materi Relasi dan Fungsi - Rahim, Essy Puspita (Universitas Nusa Cendana, 2025)
The aim of this research is to analyze and describe the mathematical communication skills of junior high school students in relation and function material. The research subjects were 22 students of SMP Muhammadiyah 4 Pekanbaru class. The type of research is descriptive qualitative with data collection in the form of written tests and interviews. The written test was in the form of a description of 3 questions. Data analysis was done through data reduction, data presentation, and conclusion drawing. The results showed that students' overall mathematical communication skills were still low with an average of 23.48%. Students achieved indicator 1 (written text) by 28.41%, indicator 2 (drawing) by 35.23%, and indicator 3 (mathematical expressions) by 7.95%. Students' difficulties occurred when converting problem information into mathematical models, explaining the solution steps coherently, and using correct mathematical language. This was caused by limited prerequisite skills, low concept understanding, and poor writing skills.